Ameliorative Effect of Green Tea Against Contrast-induced Renal Tubular Cell Injury (Iranian Journal of Kidney Diseases, 2015)
Introduction. Reactive oxygen species are a mediator of kidney damage by contrast media, and green tea is a potent-free radical scavenger. This study was designed to examine whether green tea could protect against the nephrotoxicity induced by contrast media. Materials and Methods. Forty rats were randomly divided into 4 groups. Group 1 was control; group 2 received contrast medium (intravenous iodixanol, 10 mL/kg, as a single dose); group 3 received contrast medium and then green tea extract for 3 days (10 mg/kg/d, intraperitoneal); and group 4 first received green tea and then contrast medium. Histological changes (degeneration, vacuolization of tubular renal cells, dilatation of tubular lumen, and presence of debris in the lumens) were assessed and recorded as scores from zero to 4. The sum of scores were used as the overal renal injury level. Results. Groups 3 and 4 with green tea treatment had significantly higher overall scores than the control group, but significantly lower scores than group 2 with contrast medium only. A similar trend was seen for dilatation and degeneration levels. Vacuolization level was not significantly lower in the green tea groups as compared to the contrast medium group. Debris level was not significantly lower in group 3 than group 2. The differences were not significant between groups 3 and 4.   Conclusions. We observed beneficial effect of green tea against nephrotoxicity of contrast media. Green tea extract may offer an inexpensive and nontoxic intervention strategy in patients with a risk for nephrotoxicity with contrast media.